Passive flux sampler measurements of emission rates of phthalates from poly(vinyl chloride) sheets. (1st May 2016) - Noguchi, Miyuki; Yamasaki, Akihiro
Abstract: Emission rates of bis(2-ethylhexyl)phthalate (DEHP) from poly(vinyl chloride) (PVC) sheets containing DEHP as a plasticizer at various contents (0.16%–32.3%) were measured using the passive gas flux sampling method. The gas sampler was made of Pyrex glass and had a glass fiber filter inside. The sampler was placed on the surface of a PVC sheet for a given sampling period (up to 24 h), then the DEHP captured by the glass fiber filter was determined by gas chromatography-mass spectrometry. The sampling temperature was 50 °C. The surface concentration y 0 (the DEHP concentration in the gas immediately adjacent to the surface of the PVC sheet) was determined from the experimental results and a transient DEHP emission model. The surface concentrations that were found agreed with values that have previously been published, most of which were determined in chamber emission experiments that require a longer test period than was used here. The method presented therefore allows the surface concentration y 0, which is considered to be one of the most important parameters determining SVOC emissions from solids such as PVC sheets, to be determined quickly and simply. The experimentally determined surface concentrations and the DEHP contents of the PVC sheets that were used correlated well. Graphical abstract: Schematic of the emission model. PVC = poly(vinyl chloride) and DEHP = bis(2-ethylhexyl)phthalate. Highlights: DEHP emission rates from PVC sheets were measured using passive gas flux samplers. Surface concentrations were determined using the data and a transient model. Surface concentrations matched published values (most determined using chambers). This method provides surface SVOC concentrations quickly and simply. The surface concentrations correlated well with the DEHP contents of the PVC sheets.